Experiências de mochileiros: sentidos e significados em uma dinâmica de lazer na sociedade contemporânea - Denise Falcão (2013)
This research focuses on studying backpackers on their customary trips. The central discussion point to do so is the individual and its interaction with the world which, through actions, is able to express itself changing itself and society in an alternative, reflexive and recursive way. The polycentric perspective dialogue was developed at the Interdisciplinary Graduate School of Leisure UFMG, which made it possible to enter the fields of anthropology, sociology, social psychology, tourism and leisure; a transdisciplinary approach which acknowledges the individual and evokes its incomplete, dynamic and complex dimension. The theoretical framework of this study relies on the Complex Thinking and the Cultural-Historical theories, which provided an articulation of the elements since those theories do not conceive a hierarchical arrangement in a phenomenon, but rather a dialogical interdependence among them. From such perspective, this study aimed at revealing, through the subjectivity of the individuals, the senses and significances of experiencing backpacking and what it represents to backpackers. Their history, cultural background and interaction with the contemporary world are therefore taken into account. In the process of interpreting and analyzing the data, two guiding principles were applied: the first focused on the activity itself carried out by those individuals and revealed the personal and social meanings of backpacking. The second principle confined to the individual producer of such activity, aiming at discovering the senses and significances made by backpackers and their practices. Thus, some existing concerns of this traveling practice in our contemporary society were considered and it was verified that backpackers do not see traveling as mere products of consumerism. On the contrary, they perceive it as a life experience to which they give meaning in a very particular way.